Analysis of Gut Microbiota in Patients with Breast Cancer and Benign Breast Lesions - Ma Zhijun; Qu Manli; Wang Xiaowu (Polish Journal of Microbiology, 2022)
Breast cancer (BC) and benign breast lesions (BBLs) are common diseases in women worldwide. The gut microbiota plays a vital role in regulating breast diseases’ formation, progression, and therapy response. Hence, we explored the structure and function of gut microflora in patients with BC and BBLs. A cohort of 66 subjects was enrolled in the study. Twenty-six subjects had BC, 20 subjects had BBLs, and 20 matched healthy controls. High throughput 16S ribosomal RNA (16S rRNA) gene sequencing technology was used to determine the microbial community structure. Compared with healthy individuals, BC patients had significantly lower alpha diversity indices (Sobs index, p = 0.019; Chao1 index, p = 0.033). Sobs and Chao1 indices were also lower in patients with BBLs than healthy individuals, without statistical significance (p = 0.279, p = 0.314, respectively). Both unweighted and weighted UniFrac analysis showed that beta diversity differed significantly among the three groups (p = 3.376e–14, p < 0.001, respectively). Compared with healthy individuals, the levels of Porphyromonas and Peptoniphilus were higher in BC patients (p = 0.004, p = 0.007, respectively), whereas Escherichia and Lactobacillus were more enriched in the benign breast lesion group (p < 0.001, p = 0.011, respectively). Our study indicates that patients with BC and BBLs may undergo significant changes in intestinal microbiota. These findings can help elucidate the role of intestinal flora in BC and BBLs patients.